Indonesian and American Children: Object Control Skills Comparison - Syafruddin; Bakhtiar, Syahrial; Famelia, Ruri (International Journal of Psychosocial Rehabilitation, 2020)
Empirical findings have shown the contribution of fundamental motor skills, particularly object control skills, to the physical skill levels of children as they age. However, many countries across the globe, including Indonesia, currently do not have a basic understanding of children’s fundamental motor skill profiles yet. Therefore, this study is aimed at capturing the profile of Indonesian children’s object control skills based on data from American children. Participants were 145 Indonesian children, aged 5 and 6 years (44.5% boys). Children’s object control skills were measured by using stages of developmental sequences of manipulative skills. Data from Indonesian children were compared to Age-Related Changes in Fundamental Motor Skill of Americans, which is a guideline about the age at which 60% of children perform motor skills at a specific stage. Comparative analysis showed that Indonesian children followed American children on catching and kicking development for boys. However, Indonesian boys showed lower stages of striking (71% of 5-year-old boys showed stage 2) and throwing (48% of 6-year-old boys showed stage 1) than American children (stage 3 and 5 consecutively). Furthermore, Indonesian girls showed lower stages in all object control skills, except kicking (89% of 5-year-old girls showed stage 3), while 60% of 5-year-old American children would perform stage 2 in kicking.